Addition, Reduction, and Variation of Literary Elements in Alice Adventures in Wonderland I An Analysis of Film Adaptation - Anastasia Pujo; Morada Tetty (Universitas Negeri Medan, 2022)
This study aims at finding out how film adaptation from l novel Alice Adventures in Wonderland I (1865) to the film Alice Adventures in Wonderland I 2010. In terms of addition, subtraction, and variation on its inherent elements, In the study of scientific social problems, a descriptive qualitative design is used. The researcher discovered that the film had some addition, reduction, and variation changes. These changes are also felt by the readers as a result of the film. The research findings show that there are sixteen findings for film adaptation, three findings for plot, four findings for setting, and eight findings for characters, each of which are divided into intrinsic elements of film and novel Adventures in Wonderland I.